Potential Impact of Climate Change in the Sex Ratio of Caymans in Costa Rica - Escobedo-Galván, José Armando (2012)
Ectotherm species that exhibit environmental sex determination are vulnerable to changing environmental conditions. To address how wild populations of crocodilians could potentially be affected by environmental conditions and climate change, we considered the relationship between climate variables and sex ratio in a natural population of Spectacled Caiman, Caiman crocodilus, in Caño Negro National Wildlife Refuge, in northernCosta Rica. We found a high male-biased sex ratio for the spectacled caiman in our study. Our results suggest that this bias was partly explained by increases in temperature, and decreases in precipitation associated with El Niño events in this region. Specifically, we found evidence that increased minimum air temperatures produced increased incubation temperatures, which favored production and survival of males over females. Additionally, we found that decreased precipitation was associated with increased production of males. Our results do not seem to be explained by other processes, such as differential hunting pressures, which may be more important for other crocodilian populations. We conclude that the forecasted climate change in this region will likely lead to fewer reproductive females, potentially undermining the viability of this caiman population on the long term.